Rapid hull collapse strength calculations of double hull oil tankers after collisions. (4th July 2017) - Faisal, Muhammad; Noh, Sung Hwan; Kawsar, Md. Rokan Uddin; Youssef, Samy A.M.; Seo, Jung Kwan; Ha, Yeon Chul; Paik, Jeom Kee
ABSTRACT: The primary objective of this study is to develop a rapid method for calculating hull collapse strength of double hull oil tankers after collisions. For this purpose, the statistical characteristics of hull girder collapse after collision are studied. Four double hull oil tankers with different size are considered: Panamax, Aframax, Suezmax and Very Large Crude Carrier. A set of 50 credible collision scenarios are selected by a sampling technique associated with the collision hazard identification based on the historical ship collision database. Four parameters, namely vertical collision location, damage penetration, striking ship's bulbous bow height, and striking ship's bulbous bow length are determined as a consequence of the corresponding collision scenario. The intelligent supersize finite element method is used to compute the progressive collapse behaviour of hull girder structures with the collision damages so determined. The residual hull girder strength indices can then be determined and formulated in a closed expression associated with collision damages and ship length. The developed formulations will be useful to quickly calculate the hull collapse strength of double hull oil tankers immediately after collisions.